Tolerance mechanism of Trichoderma asperellum to Pb2+: response changes of related active ingredients under Pb2+ stress. Issue 9 (31st January 2020) - Sun, Huiqing; Wu, Lingran; Hao, Yali; Liu, Chunyu; Pan, Lichao; Zhu, Zhenyuan
Abstract : Trichoderma asperellum ZZY has good tolerance to Pb 2+, but the tolerance mechanism is not clear. Abstract : Trichoderma asperellum ZZY has good tolerance to Pb 2+, but the tolerance mechanism is not clear. The manuscript aimed to clarify the tolerance mechanism from the perspective of the response changes of related active ingredients. The synthesis of polysaccharides, proteins and thiol compounds in Trichoderma asperellum can be accelerated with Pb 2+ stress. Under Pb 2+ stress, Trichoderma asperellum can synthesize oxalic acid and secrete it extracellularly. In addition, high concentration of Pb 2+ can inhibit the synthesis and extracellular secretion of formic acid and malic acid. The tolerance of Trichoderma asperellum to Pb 2+ is the results of multiple reactions. The Pb 2+ can promote the synthesis of polysaccharides, proteins, thiol compounds and oxalic acid. In the early stage of Pb 2+ stress, Trichoderma asperellum can rapidly initiate an extracellular emergency mechanism, synthesize oxalic acid in mycelia and secrete it extracellularly to remove free Pb 2+ and alleviate the toxicity of Pb 2+ to cells. With the transport of Pb 2+ into cells, it can promote the synthesis of polysaccharides, proteins, thiol compounds to adsorb and transform the Pb 2+ and ease the damage to the cells. The manuscript provides theoretical support and scientific explanation for the application of Trichoderma asperellum .